The nature of anger in people with multiple sclerosis: a qualitative study. Issue 7 (2nd July 2020) - Laing, Christianne M.; Cooper, Clare L.; Summers, Fiona; Lawrie, Louisa; O'Flaherty, Shibeal; Phillips, Louise H.
Abstract: Objective: People with multiple sclerosis (pwMS) who experience higher levels of anger also report poorer quality of life (QoL). This qualitative study explored the subjective experience of anger amongst pwMS, and how anger influenced their lives. Methods: A series of semi-structured, face-to-face interviews were conducted with 20 pwMS. Interviews were recorded, transcribed and then Interpretative Phenomenological Analysis was used to analyse the emerging themes. Results: The most common experience of anger was frustration that MS-related symptoms restricted participation in everyday activities. Also, some experiences of anger-with-self were focused on frustration at the inability to overcome symptom-related activity limitations. Participants reported frustration with others' insensitivity to the effects of the disease process, as well as usual daily irritations with family and colleagues. Some of the participants reported the use of coping strategies to deal with anger episodes. Conclusion: Many pwMS experience frustration at the restrictions that the disease places on them, self-directed anger, and irritation with others' attitude towards them. Much research in MS focuses on physical symptoms, but current results indicate that there is a need to better understand the emotional challenges faces by pwMS, and to provide more support for those who are experiencing frustration.